The Role of the Gastrointestinal System in Neuroinvasion by SARS-CoV-2 - Xu, Jiali; Wu, Zifeng; Zhang, Mi; Liu, Shijiang; Zhou, Ling; Yang, Chun; Liu, Cunming (Frontiers in Neuroscience, 2021)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is one of the most devastating pandemics in history. SARS-CoV-2 has infected more than 100 million people worldwide, leading to more than 3.5 million deaths. Initially, the clinical symptoms of SARS-CoV-2 infection were thought to be restricted to the respiratory system. However, further studies have revealed that SARS-CoV-2 can also afflict multiple other organs, including the gastrointestinal tract and central nervous system. The number of gastrointestinal and neurological manifestations after SARS-CoV-2 infection has been rapidly increasing. Most importantly, patients infected with SARS-CoV-2 often exhibit comorbid symptoms in the gastrointestinal and neurological systems. This review aims to explore the pathophysiological mechanisms of neuroinvasion by SARS-CoV-2. SARS-CoV-2 may affect the nervous system by invading the gastrointestinal system. We hope that this review can provide novel ideas for the clinical treatment of the neurological symptoms of SARS-CoV-2 infection and references for developing prevention and treatment strategies.